Experimental phase diagram, thermodynamic modeling and solidified microstructure in the Mo–Ni–W ternary system. (March 2020) - Tang, Meifang; Du, Yong; Zhou, Peng; Wang, Shimin; Zhang, Huaqing; Zeng, Yinping; Liu, Shuhong; Chai, Xueyuan; Peng, Yingbiao; Wu, Changjun; Su, Xuping; Liu, Zi-Kui
Abstract: In this work, the isothermal section at 900 °C, a liquidus projection and invariant reaction temperatures in the Mo–Ni–W ternary system were established using X-ray diffraction (XRD), Differential Scanning calorimeter (DSC) and electron probe micro-analysis (EPMA). Based on the experimental phase diagram data from the present work and the literature, the Mo–Ni–W system was assessed by means of the CALPHAD (CALculation of PHAse Diagrams) method. The liquid, fcc-(Ni), bcc-(Mo) and bcc-(W) phases were described with a regular solution model. The sub-lattice models were used to express Gibbs energies of the intermediate phases of MoNi3, MoNi, (Mo, W)Ni4, WNi and W2 Ni. The present modeling covers the entire composition and an extensive temperature ranges of the Mo–Ni–W ternary system, and a set of self-consistent thermodynamic parameters were finally obtained. Comprehensive comparisons between the calculated and measured phase diagram data show that most experimental information is satisfactorily accounted for by the present thermodynamic description. Scheil solidification simulations for a few representative as-cast alloys were performed. It was found that the solidified microstructures can be reasonably described by the Scheil simulation. The liquidus projection and reaction scheme of the Mo–Ni–W system were generated by the presented modeling.